ANALISIS PEMBELAAN HAK MILIK TERGUGAT DALAM SENGKETA PERJANJIAN JUAL BELI TOKO DI PLAZA BUKITTINGGI - Rabiul Fadjri; Anggun Lestari Suryamizon; Mahlil Adriaman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This case involved a dispute over a sale and purchase agreement that was heard by the Bukittinggi District Court under number 2/Pdt.G/2022/PN Bkt. The defendant was charged with unlawful conduct, but defended himself by arguing that his actions could not be categorized as unlawful. The essence of the problem in this dispute is that the plaintiff denies the existence of a sale and purchase agreement, which is the basis of the claim. The formulation of the problem of this research is to find out how the defense of the defendant I’s property rights in the face of the verdict and what defense theory is used, as well as the consideration of the panel of judges in deciding the case. The research method used is the Descriptive method with a Normative Juridical approach, which only uses written regulations from the library as a secondary data source. The results showed that Article 1918 of the Civil Code gives the opposing party the right to submit counter proof to a decision that has permanent legal force. In defending property rights, there are several important elements that can be considered, such as proof of ownership, breach of agreement/contract, and violation of law or procedure.